Effectiveness of the Use of Facilities at the Bureau of People's Walfare, North Sumatera Province Governor's Office - Sri Rahayu Ayu; Nurhayati Nurhayati (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The research is to know whether Facility (computer, office working, transportation, electicity) influence to civil servant performance (work procces, working condition, time in work, number of mistakes, amount in job type, job quality punctuality, ability work, evaluating ability). At the education office of north Sumatera Governor's. The use of Facilities Will determine how the quality of employee performance, so that for the realization of a quality organization it ia necessary to provide good Facilities.